2013
DOI: 10.1177/0193945913484987
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Bereaved Families’ Decisions About Organ Donation

Abstract: This article reports on the process and outcomes of a systematic integrative literature review, designed to enhance understanding of the factors influencing bereaved families' decisions to agree or decline the donation of their deceased relative's organs for transplantation. Research originating from eight Western countries (N = 20 studies) provided an international perspective to the review. Thematic analysis and synthesis of textual data culminated in the development of three global themes (past, present, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 34 publications
1
111
0
2
Order By: Relevance
“…In hospital, knowledge and inferences about the deceased’s and family members’ preferences influence family experience (Falomir-Pichastor et al, 2013). Cause of death is important too, and Walker et al (2013) described intense emotional responses to sudden death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospital, knowledge and inferences about the deceased’s and family members’ preferences influence family experience (Falomir-Pichastor et al, 2013). Cause of death is important too, and Walker et al (2013) described intense emotional responses to sudden death.…”
Section: Resultsmentioning
confidence: 99%
“…Complex relationships exist between variables of the in-hospital process (Walker et al, 2013), and studies highlight the need for a comprehensive understanding of the experience (Falomir-Pichastor et al, 2013). However, although a number of studies have explored ways of assisting families to make an informed decision about donation, provision of grief support and identifying ways of assisting families to commence their bereavement meaningfully have received less attention (De Groot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…People who agree to be organ donors, both families of the deceased and those who register as potential donors, describe their motivation as mainly based on wanting to help others in need (Shaw & Webb, ). Donor family members might add that they find comfort in the thought of the deceased's organs “continuing” to live after their death (Walker, Broderick, & Sque, ). Organ donors are viewed as “good people” or as altruistic in public opinion surveys (Lauri & Lauri, ) and depicted positively in newspaper articles (Feeley & Vincent, ), web videos (Tian, ), and in entertainment media (Morgan, Harrison, Long, et al, ).…”
Section: Altruism As a Contested Conceptmentioning
confidence: 99%
“…More recent work has linked the timing of the donation request to family member's agreement or disagreement to donation [15], and studies reporting factors that influence family members' decision-making have included the timing of the request [16][17][18][19]. A systematic review carried out by Simpkins et al in 2009 [20] indicated that the timing of the request for organ and tissue donation was one of the main modifiable factors (others are listed) associated with consent or refusal for organ donation by relatives.…”
Section: The Timing Of the Request For Donationmentioning
confidence: 99%